Molecular dynamics simulation of graphene on Cu (1 0 0) and (1 1 1) surfaces. (February 2015) - Klaver, T.P.C.; Zhu, Shou-En; Sluiter, M.H.F.; Janssen, G.C.A.M.
Abstract: We present results of molecular dynamics simulations of graphene on Cu surfaces. Interactions were modelled with the charge-optimized many-body potential, which gives a reasonable though not flawless description of the graphene–Cu system. The interaction between Cu and complete graphene sheets is characterized by an 'averaged out' interaction at a large bonding distance. Many bonding characteristics are indifferent to the details of how the Cu surface atoms are arranged, including the surface orientation and even if the surface is solid or molten. Graphene edges have a strong interaction with the Cu substrates. Systems were modelled at various temperatures, ranging from 0 K to the Cu melting temperature. At high temperature we find that the presence of graphene slightly stabilizes the Cu surface and retards surface melting. After cooling down to room temperature, the Cu substrate is 1.7% smaller than the graphene due to difference thermal expansion coefficients. This leads to the formation of wrinkles in graphene. Single wrinkles experience only small migration barriers and are quite mobile. When multiple wrinkles intersect, they form immobile knots that hinder further movement of the connected wrinkles. The elastic energy of the wrinkles and knots due to bending of the graphene is determined.